Leitura crítica de um livro didático de língua portuguesa : reflexões sobre aspectos coloniais em autorias de textos - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
This paper aims to carry out a critical reading of the textbook – ‘‘Português trilhas e tramas’’ (SETTE. et al, 2016) – volume 1, aiming to problematize characteristics of the material that are not consistent with a critical perspective of linguistic education. By sharing the understanting that to produce critical linguistic and educational analyzes in a subaltern society, we need to think from decoloniality (QUEIROZ, 2020), the concept of linguistic education that I adopt form my critical reading also encompasses decolonial thinking. The book analyzed is part of a collection distributed by the National Textbook Program (PNLD), which is used in seven high schools in the northwest region of the Goiás’ state, some of which are internship field school of one of the Letters course from the State University of Goiás. This is a qualitative and documentary study (CELLARD, 2008), which also follows investigative characteristics of the analysis of the empirical material, with investigative characteristics of Ginzburg's (1989) evidential paradigm. For the analysis of the empirical material, I rely on praxiologies of the inter/transdisciplinary field of Critical Applied Linguistics (MOITA LOPES, 2006; PENNYCOOK, 2006, RAJAGOPALAN, 2006), with an emphasis on linguistic education (PESSOA, 2018) and on the analysis of language textbooks (ANJOS, 2017; CONTI E MASTRELLA-DE-ANDRADE, 2015; FERREIRA, 2014, 2020; LOUSADO, 2020; NASCIMENTO, 2016), interconnected with theorizations on coloniality/decoloniality (LUGONES, 2008; MALDONADO-TORRES, 2007 MIGNOLO, 2003, 2009; QUEIROZ, 2020; QUIJANO, 2007) and also on racism, gender and intersectionality (AKOTIRENE, 2019; LOURO, 1997; MUNIZ, 2020; RIBEIRO, 2017). Among the results, I discuss about signs of continuity of a colonial conception of education in textbooks, characterized mainly by the predominance of texts, whose authors are white men from southeastern Brazil. In this discussion, I emphasize the invisibility of black women as a producer of knowledge in textbooks, as well as the need to disseminate texts produced by non-white and cisheteropatriarchal groups, as a way to break with the currents of hegemonic colonizing patriarchy.
Critical reading of a portuguese language book: reflections on colonial aspects in texts' authorship
Keywords: Livro didático; Educação linguística crítica; Decolonialidade; Textbook; Critical linguistic education; Decoloniality; LINGUISTICA, LETRAS E ARTES; LINGUISTICA::LINGUISTICA APLICADA